Characterization of Two Loss-of-Function NF1 Variants in Chinese Patients and Potential Molecular Interpretations of Phenotypes - Zhang, Tingting; Han, Tianting; Dong, Zhiya; Li, Chuanyin; Lu, Wenli (Frontiers in Genetics, 2021)
Neurofibromatosis type 1 (NF1) is a common genetic disorder characterized by cafe´-au-lait spots, skinfold freckles, the formation of neurofibromas, skeletal dysplasia, vascular dysplasia, and an increased risk of malignant tumors. In this study, two Chinese NF1 children troubled with bone lesions or hypertension were reported. A de novo NF1 mutation (c.4925T>A/p.V1642E) and a maternally inherited NF1 mutation (c.4883T>A/p.L1628*) were identified by molecular sequence. According to the ACMG/AMP guidelines, the c.4925T>A was classified as variants of uncertain significance (VOUS) while the c.4883T>A mutation was identified as likely Pathogenic. Further study found that these two NF1 mutants had lost their function to inhibit the Ras/Erk signaling and the proliferation of cells, which could interpretate some phenotypes of these two NF1 patients. We also observed these two NF1 mutants displayed decreased protein stability with increased ubiquitination levels compared with that of wild-type NF1.